EVALUATION OF DIVERSITY OF FREE LIVING PLANT GROWTH PROMOTING RHIZOBACTERIA OF WHEAT GROWN IN SALINE SOIL - SHUKLA, UMESH KUMAR; KUMAR, ADESH; SRIVASTAVA, DIVYA (The Bioscan, 2015)
A study was conducted to find out the microbial diversity of the rhizosphere of wheat and screening of the effective PGPR isolate with multiple traits under saline soil conditions. Total 59 rhizobacteria were isolated from rhizosphere using different media viz., NA, King’s B medium, and Jensen’s medium while predominant genera found were Pseudomonas, Bacillus and Azotobacter. All the isolates were screened in vitro for their plant growth promoting traits. Ammonia production was most common trait of Pseudomonas (37.03%) and Azotobacter (100.00%) and Bacillus (100.00%). Phosphorus solubilization was detected in the isolates of Azotobacter (66.23%), Pseudomonas (45.35%), and Bacillus (23.80%). Thirty seven (63%) isolates restricted the growth of the test fungus Alternaria alternate. Twelve isolates (four isolates from each medium) were selected on the basis of qualitative screening for plant growth promoting traits. The amount of IAA produced by selected isolates was in the range of 63.60µg/ml to 306.60µg/ml. The selected isolates were also tested for salt (NaCl) tolerance at 3% to 10% concentration and found Pseudomonas (75%) Bacillus (75%) and Azotobacter (100%) isolates tolerant at 10% NaCl concentration . With this work it can be concluded that the rhizobacteria isolated from the rhizospheric soils of wheat would be useful as inoculants for saline soil conditions.